2016
DOI: 10.1002/ppul.23511
|View full text |Cite
|
Sign up to set email alerts
|

Rural residence, farming environment, and allergic diseases in Argentinean adolescents

Abstract: Rationale Little is known about residence in a rural or farming environment and allergic diseases in Latin America. Methods Cross-sectional study of rural residence and current wheeze, current asthma and current symptoms of allergic rhino-conjunctivitis in 1,804 adolescents (ages 13–14 years) attending 31 schools in urban and rural areas of San Francisco (Córdoba, Argentina). Rural residence was classified as never, previous, and current. Duration of rural residence was categorized as 0, >0 but ≤ 5 years, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Children who had migrated after 3 years of age had an increased risk of developing wheeze compared to non-migrants and migrants with less than 5 years of residence in their host city had a higher prevalence of wheeze compared to non-migrants. Another study on adolescents aged 13–14 years in an urban area of Argentina showed that the adolescents with a history of rural residence had the same rates of wheeze as compared to those who had been living in urban areas [37]. …”
Section: First-generation International Immigrantsmentioning
confidence: 99%
“…Children who had migrated after 3 years of age had an increased risk of developing wheeze compared to non-migrants and migrants with less than 5 years of residence in their host city had a higher prevalence of wheeze compared to non-migrants. Another study on adolescents aged 13–14 years in an urban area of Argentina showed that the adolescents with a history of rural residence had the same rates of wheeze as compared to those who had been living in urban areas [37]. …”
Section: First-generation International Immigrantsmentioning
confidence: 99%
“… 28 Another study conducted in an urban area of Argentina showed that adolescents aged 13–14 years with a history of rural residence had the same prevalence of wheeze compared with those who had always lived in the urban area. 29 Our study focused on the effects of internal migration on wheeze prevalence in an urban population of an LMIC, where migrants formed a diverse group including migrants from rural communities, migrants from other urban settings, and those crossing voluntarily or being displaced by civil conflict across the international border with Colombia ( figure 1 ). In this setting, we found that rural to urban migration is an important determinant of a higher risk of wheeze in an urban population.…”
Section: Discussionmentioning
confidence: 99%
“…However, migrant health may deteriorate with increasing length of residence in the new country. 29 In the case of rural to urban migration, evidence for a healthy migrant effect is limited. 31 In our study, socioeconomic variables of the migrant population were not statistically different than those of the non-migrant population.…”
Section: Discussionmentioning
confidence: 99%
“…This protective effect against allergic diseases may be explained by bacterial or fungal exposures resulting from contact with livestock or animal feed/shed and raw milk consumption among children living in farms 35, 36 . A few studies in Latin America have also shown rural residence to be associated with lower risk of current wheeze and allergic rhino-conjunctivitis 14, 37, 38 . In an exploratory analysis conducted as part of a study of Mexican American children, antibiotic use was associated with asthma or current wheeze in children who were born in rural areas of Mexico, but not in those born in urban areas of Mexico 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we reported that rural residence was associated with reduced odds of current wheeze and allergic rhino-conjunctivitis among adolescents (ages 13 to 14 years) living in the province of Córdoba (Argentina) 14 . Given that finding, as well as a prior report of potential effect modification of the effect of antibiotic use on atopy by presence of animals (pets) in the home 8 , we hypothesized that antibiotic use would affect the risk of atopic diseases (current wheeze or allergic rhino-conjunctivitis) among children living in urban areas in early life, but not among those living in rural areas in early life (who are often exposed to farm animals and pets, and thus may be less susceptible to the detrimental effects of antibiotics by virtue of a richer and more robust gut microbiota).…”
Section: Introductionmentioning
confidence: 92%